2020
DOI: 10.1111/tid.13296
|View full text |Cite
|
Sign up to set email alerts
|

Case report: A kidney transplant patient with mild COVID‐19

Abstract: Coronavirus Disease 2019 (COVID‐19) is currently a pandemic with a mortality rate of 1%‐6% in the general population. However, the mortality rate seems to be significantly higher in elderly patients, especially those hospitalized with comorbidities, such as hypertension, diabetes, or coronary artery diseases. Because viral diseases may have atypical presentations in immunosuppressed patients, the course of the disease in the transplant patient population is unknown. Hence, the management of these patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 21 publications
1
55
0
1
Order By: Relevance
“…A review of available renal transplant cases can be found in Table 1. 4,7,[10][11][12][13][14][15] Overall, our patient did well without experimental antiviral or anti-inflammatory therapies and experienced no serious complications, including need for hospitalization or supplemental oxygenation. In fact, the patient appeared well enough that the ED did not order labs beyond respiratory virus and SARS-CoV-2 testing.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A review of available renal transplant cases can be found in Table 1. 4,7,[10][11][12][13][14][15] Overall, our patient did well without experimental antiviral or anti-inflammatory therapies and experienced no serious complications, including need for hospitalization or supplemental oxygenation. In fact, the patient appeared well enough that the ED did not order labs beyond respiratory virus and SARS-CoV-2 testing.…”
Section: Discussionmentioning
confidence: 66%
“…There have been reported cases of COVID-19 in HIV-infected patients and cases of COVID-19 in transplant recipients. [4][5][6][7][8][9][10][11][12][13][14][15] However, this case is the first detailed report of an HIV-positive kidney transplant recipient who developed and recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 84%
“…Among the smaller case series and individual case reports, notable findings included SOT recipients with COVID‐19 who were early in their posttransplant course and had favorable outcomes 18‐20 . Authors from Italy describe their experience with 6 liver transplant patients, among whom 3 were less than 2 years posttransplant and had mild disease, whereas the 3 who were > 10 years from transplant died 20 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…One unresolved issue about COVID-19 is the influence of immunosuppressive treatments (ISTs) on disease occurrence and course. The results published so far are rather contradictory, with authors reporting either mild [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ] or severe disease course with high mortality [ 13 , 14 , 15 , 16 , 17 , 18 ]. These differences could be due to the different approaches adopted for therapy management (continuation or interruption of ISTs).…”
Section: Introductionmentioning
confidence: 99%